Are life-history traits equally affected by global warming? A case study combining a multi-trait approach with fine-grain climate modeling. (August 2019) - Iltis, Corentin; Louâpre, Philippe; Pecharová, Karolina; Thiéry, Denis; Zito, Sébastien; Bois, Benjamin; Moreau, Jérôme
Graphical abstract: Highlights: We simulated global warming using in situ climatic data and climate models. We tracked the responses of an insect's traits to this experimental warming. Warming positively influenced development, survival and escape ability from enemies. It adversely affected stored lipid reserves and immunity (phenoloxidase activity). This implies complex consequences of warming for population and trophic dynamics. Abstract: Predicting species responses to climate change requires tracking the variation in individual performance following exposure to warming conditions. One ecologically relevant approach consists of examining the thermal responses of a large number of traits, both related with population dynamics and trophic interactions (i.e. a multi-trait approach). Based on in situ climatic data and projections from climate models, we here designed two daily fluctuating thermal regimes realistically reflecting current and future conditions in Eastern France. These models detected an increase in mean temperature and in the range of daily thermal fluctuations as two local facets of global warming likely to occur in our study area by the end of this century. We then examined the responses of several fitness-related traits in caterpillars of the moth Lobesia botrana – including development, pupal mass, survival rates, energetic reserves, behavioral and immune traits expressed against parasitoids – to this experimental imitation of global warming. Increasing temperatures positively affected development (leading to a 31% reduction in the time needed to complete larval stage), survival rates (+19%), and movement speed as a surrogate for larval escape ability to natural enemies (+60%). Conversely, warming elicited detrimental effects on lipid reserves (−26%) and immunity (total phenoloxidase activity: −34%). These findings confirm that traits should differ in their sensitivity to global warming, underlying complex consequences for population dynamics and trophic interactions. Our study strengthens the importance of combining a multi-trait approach with the use of realistic fluctuating regimes to forecast the consequences of global warming for individuals, species and species assemblages.